Glucolipotoxicity age-dependently impairs beta cell function in rats despite a marked increase in beta cell mass - Fontés, G. (2010)
AIMS/HYPOTHESIS: Prolonged exposure of pancreatic beta cells to excessive levels of glucose and fatty acids, referred to as glucolipotoxicity, is postulated to contribute to impaired glucose homeostasis in patients with type 2 diabetes. However, the relative contribution of defective beta cell function vs diminished beta cell mass under glucolipotoxic conditions in vivo remains a subject of debate. We therefore sought to determine whether glucolipotoxicity in rats is due to impaired beta cell function and/or reduced beta cell mass, and whether older animals are more susceptible to glucolipotoxic condition. METHODS: Wistar rats (2 and 6 months old) received a 72 h infusion of glucose + intravenous fat emulsion or saline control. In vivo insulin secretion and sensitivity were assessed by hyperglycaemic clamps. Ex vivo insulin secretion, insulin biosynthesis and gene expression were measured in isolated islets. Beta cell mass and proliferation were examined by immunohistochemistry. RESULTS: A 72 h infusion of glucose + intravenous fat emulsion in 2-month-old Wistar rats did not affect insulin sensitivity, insulin secretion or beta cell mass. In 6-month-old rats by contrast it led to insulin resistance and reduced insulin secretion in vivo, despite an increase in beta cell mass and proliferation. This was associated with: (1) diminished glucose-stimulated second-phase insulin secretion and proinsulin biosynthesis; (2) lower insulin content; and (3) reduced expression of beta cell genes in isolated islets. CONCLUSIONS/INTERPRETATION: In this in vivo model, glucolipotoxicity is characterised by an age-dependent impairment of glucose-regulated beta cell function despite a marked increase in beta cell mass.